Implementation of a One-Stop Integrated Service Policy at the Kotamobagu City One-Stop Investment and Integrated Service Office - Sompotan, Meike R.; Kairupan, Sisca B.; Pangkey, Itje (Technium Social Sciences Journal, 2025)
The purpose of the research is to find out, analyze, and describe the extent to which the One-Stop Integrated Service (PTSP) Policy Implementation is implemented at the Kotamobagu City Investment and One-Stop Integrated Service Office (DPMPTSP). This research uses a qualitative method. The number of respondents was 11 people who were determined by purposive sampling technique. This research is focused on how the implementation of a one-stop integrated service policy in managing Building Approval Permits organized by the community by looking at indicators of socialization of rules, mechanisms and procedures, and willingness (commitment to the implementation of a one-stop integrated service policy). The results showed that one-stop integrated services, especially in the issuance of Building Approval Permits (PBG), have been implemented well. Processing and responsible officers include the Head of the Service Office, the Head of the Licensing Service Agency, and the officers of the processing section or counter are competent in their respective fields. Personnel, especially in the processing section, are still limited while the number of incoming applicant files increases every day. Socialization has run quite well and facilities and infrastructure to support the implementation of licensing services are also quite good and provide a sense of comfort for people who will carry out the licensing process. The establishment of standard operating procedures has been fulfilled. However, there are still some problems in the procedure for implementing licensing services that are not in accordance with the SOP, namely the untimely issuance of letters.